ANALISIS KARAKTERISTIK METIL ESTER (BIODIESEL) MINYAK KEMIRI SEBAGAI ALTERNATIF BIOADITIF PENURUN TITIK TUANG BIODIESEL CPO - Misdawati, Misdawati; Siswadi, Siswadi; Farah Dina, Sari (BAROMETER, 2024)
One of the drawbacks of Crude Palm Oil (CPO) biodiesel is that it has a high pour point which causes disadvantages in its use. The objective of this research was to obtain biodiesel of low pour point by mixing CPO biodiesel with Candlenut biodiesel with various ratios among them. In this research, the effect of biodiesel composition, and the type of biodiesel in the mixture were evaluated in order to obtain the best combination of the biodiesel in the mixture. The influence of polyunsaturated such as linolenic derived from candlenut oil was also evaluated. The result of the research showed that when the amount of the Candlenut biodiesel increased in the mixture the pour point decreased. When the ratio between CPO and Candlenut biodiesel was 80:20, the product had an optimal pour point of – C. In fact, .the number of double bonds present in linolenic acid had a more significant effect on the quality of biodiesel produced than the length of the fatty acid chain.